GAYA BERCERITA MENGGUNAKAN MAJAS ALEGORI PADA IKLAN LAYANAN MASYARAKAT “GUNAKAN HELM SECARA BIJAK” - Annisa Pertiwi Ramadhanti (Saraswati)
Advertising on television media is a communication message that aims tointroduce a product or service. The next goal is to motivating and persuading theviewers or audiences to find, buy and become regulars. Public service ads are adsthat have goal to persuading the public. Motor vehicle is one of the transportationthat Indonesian people use. The large number of motor vehicle makes the risk of roadaccidents increases. A helmet is one of the protection things to protect the driverhead when accidents happen. To inform the importance of using helmets, a programcalled advertisement made. Therefore, to develop a public service announcement thatcan deliver a message, is needed an alternative to delivery a message using a figureof speech. Keywords: helmet, commercials, public service announcements, figure of speech